2016
DOI: 10.1016/j.neurobiolaging.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Strong association between glucocerebrosidase mutations and Parkinson's disease in Sweden

Abstract: Several genetic studies have demonstrated an association between mutations in glucocerebrosidase (GBA), originally implicated in Gaucher's disease, and an increased risk of Parkinson's disease (PD). We have investigated the possible involvement of genetic GBA variations in PD in the Swedish population. Three GBA variants, E326K, N370S, and L444P were screened in the largest Swedish Parkinson cohort reported to date; 1625 cases and 2025 control individuals. We found a significant association with high effect si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 51 publications
0
32
1
1
Order By: Relevance
“…The allele frequency of the two mutations is high among Ashkenazi Jewish PD patients with a total frequency of 15.3%. The combined frequency of the two mutations is approximately 3.2% in non-Ashkenazi Jewish PD patients [8], 2.3% in Norwegian patients [8] and 2.8% in Swedish patients [19], whereas among non-Finnish Europeans in the ExAC database the frequency is 0.8%. We found these GBA mutations in 2.8% of the EOPD patients giving a relative risk of 3.8 for PD and in 1.9% of the LOPD patients giving a relative risk of 2.5.…”
Section: Discussionmentioning
confidence: 99%
“…The allele frequency of the two mutations is high among Ashkenazi Jewish PD patients with a total frequency of 15.3%. The combined frequency of the two mutations is approximately 3.2% in non-Ashkenazi Jewish PD patients [8], 2.3% in Norwegian patients [8] and 2.8% in Swedish patients [19], whereas among non-Finnish Europeans in the ExAC database the frequency is 0.8%. We found these GBA mutations in 2.8% of the EOPD patients giving a relative risk of 3.8 for PD and in 1.9% of the LOPD patients giving a relative risk of 2.5.…”
Section: Discussionmentioning
confidence: 99%
“…Нами проведено исследование особенностей клинического течения у пациентов с мутациями (N370S, L444P) и полиморфными вариантами (E326K, T369M) гена GBA. Показано, что частота БП, ассоциированная с наличием скринируемых генетических вариантов гена GBA, соответствует данным, полученным в европейских популяци-ях [21,22]. Более раннее начало заболевания по сравнению со сБП было выявлено у пациентов с мутациями, но не с полиморфными вариантами гена GBA, что соответствует полученным ранее результатам [13].…”
Section: Discussionunclassified
“…It has been recently shown that especially rare genetic variants, such as homozygous variant defects resulting in rare pathologies, can associate for increased risk of more common maladies as well. For example, having a pathogenic GBA mutation for Gaucher's Disease (GD) (e.g., N370S, L444P) in one allele (carrier) will not usually manifest the full symptoms of GD, but does increase risk for Parkinson's disease . The odds ratio for the GBA mutation in PD was greater than 5, which is unusually high compared to risk loci found from GWAS .…”
Section: Ipscs To Understand Genetic and Phenotypic Variations Beyondmentioning
confidence: 97%